2010
DOI: 10.1242/jeb.050807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin infusion on glucose homeostasis and glucose metabolism in rainbow trout fed a high-carbohydrate diet

Abstract: SUMMARYThe origin for the poor glucose utilization in carnivorous fish species fed high carbohydrate diets remains under debate. In the present study, we have fed rainbow trout a diet containing 30% carbohydrate for 1 or 5 days. In both cases, fish were implanted with mini-osmotic pumps releasing 0.7i.u.kg -1 day -1 bovine insulin, and mRNA transcripts and the protein phosphorylation status of proteins controlling glycemia and glucose-related metabolism were studied in fish killed 6h after the last meal. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…Current information shows that insulin plays a major role in blocking R a glucose in animals undergoing acute elevation in glycemia. In mammals as well as trout, hepatic production is decreased when high insulin levels inhibit glucose release in the circulation by terminating the transcription of glucose 6-phosphatase (G6Pase) (Polakof et al, 2010a;Rojas and Schwartz, 2014 mammals (Shrayyef and Gerich, 2010). Similarly, gluconeogenesis is inhibited by high levels of insulin, which inhibits transcription of mammalian phosphoenolpyruvate carboxykinase (PEPCK) (Rojas and Schwartz, 2014).…”
Section: Suppression Of Hepatic Glucose Productionmentioning
confidence: 99%
“…Current information shows that insulin plays a major role in blocking R a glucose in animals undergoing acute elevation in glycemia. In mammals as well as trout, hepatic production is decreased when high insulin levels inhibit glucose release in the circulation by terminating the transcription of glucose 6-phosphatase (G6Pase) (Polakof et al, 2010a;Rojas and Schwartz, 2014 mammals (Shrayyef and Gerich, 2010). Similarly, gluconeogenesis is inhibited by high levels of insulin, which inhibits transcription of mammalian phosphoenolpyruvate carboxykinase (PEPCK) (Rojas and Schwartz, 2014).…”
Section: Suppression Of Hepatic Glucose Productionmentioning
confidence: 99%
“…Insulin receptors are present in the major insulin-responsive tissues, including white muscle, liver, and adipose tissues (4,11,27), and upregulation of insulin-binding and tyrosine kinase activities is observed after insulin treatment and carbohydrate-rich diets, respectively (2,11,27). Moreover, we have recently demonstrated that both fasted and high-carbohydrate-fed rainbow trout respond to increased circulating exogenous insulin levels and that insulin improved glucose distribution and uptake by peripheral tissues, enhancing the capacity of the animal to deal with a glucose load (31,32).…”
mentioning
confidence: 96%
“…In primary cell culture of rainbow trout hepatocytes, insulin is able to stimulate GK gene expression, but the presence of amino acids seems to be necessary; otherwise, GK gene expression is repressed by insulin Lansard et al, 2010b). The inhibitory effect of insulin on GK gene expression was further confirmed in vivo following acute intraperitoneal administration of insulin or chronic infusion of insulin (4 days) in both fasted and high-carbohydrate fed fish (Polakof et al, 2010b(Polakof et al, , 2010d. The in vivo repression of GK gene by insulin in trout liver represents a paradoxical regulation in a fish species in which the natural carbohydrate intake is very low and the insulin secretion is well stimulated in fish fed high carbohydrate diets (Capilla et al, 2003).…”
Section: Glycolysismentioning
confidence: 87%
“…In rainbow trout, acute administration of insulin failed to stimulate PK gene expression in liver Polakof et al, 2010d), whereas it faintly decreased PK mRNA level in skeletal muscle. When insulin is chronically administered to fasted and high-carbohydrate rainbow trout using osmotic pumps, PK gene expression becomes slightly reduced in liver but no more different from saline-treated fish in muscle (Polakof et al, 2010b(Polakof et al, , 2010d. All these data indicate that in vivo, exogenous insulin poorly affect PK gene expression.…”
Section: Glycolysismentioning
confidence: 92%
See 1 more Smart Citation